Pertarungan Elite Lokal dalam Menentukan Sistem Pemerintahan Nagari di Kabupaten Agam - Ujang Wardi; Aidinil Zetra; Asrinaldi. Asrinaldi. (ARISTO, 2019)
The presence of Law No. 6 of 2014 as a form of central recognition of the regions, provides new opportunities for elitees at the local level in determining the choice of "berdesa", "berdesa adat" or "kelurahan". What is meant by the local elitee is the adat elitee (ninik mamak) and the government elitee (non ninik mamak, 'they are the generation born in the 1970s, presumably not understanding the concept of nagari, and more absorbing the concepts of modernization'). This conception is the space in arranging the nagari for the local elitee in Minangkabau as a form of the inability of Law No. 22 of 1999 and Law No. 32 of 2004 which has been accommodating the central interest to the local. In its praxis, Law No. 6 of 2014 encourages the dynamics of political interest at the local level with the existence of two distinct interests between the adat elitee and the government elitee who have held the power at the local level. This study uses the qualitative method with case study approach. The results of this study indicate the attractiveness of elitee interests at the local level, in the choice between the administrative-based of nagari and the adat-based of nagari. The attractiveness is based on two interests between philosophical interests and pragmatic interests for power. Regardless of the two interests that occurred, Law no. 6 of 2014 is a momentum for local elitees to gain legitimacy and authority, as a form of recognition gained by local elitees.